Metode Pembelajaran dalam Pendidikan Islam: Strategi, Pendekatan, dan Tantangan di Era Digital - Arhmawati, Ruth Alvadira; R., Sabrina Azzahroh J.; Faizin, Moh. (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
Islamic education plays a fundamental role in shaping students’ personality, morality, and mindset so that they become insan kamil—individuals who are knowledgeable, faithful, and virtuous. This article provides a comprehensive discussion of teaching methods, strategies, approaches, and standardization in Islamic education within the digital era. The study employs a qualitative approach through library research, analyzing academic literature, journals, and previous studies. Findings reveal that the effectiveness of Islamic education depends on the synergy of four key components: methods, strategies, approaches, and standardization. Teaching methods include habituation, memorization, practice, interactive lectures, and blended learning. These methods function not only as tools for knowledge transfer but also as means of internalizing moral and spiritual values. Learning strategies emphasize the integration of Islamic values with modern contexts, adaptation to technology, and participatory approaches that encourage active student involvement. Contextual and humanistic approaches strengthen the relevance of Islamic teachings to contemporary social and cultural dynamics. The integration of digital technology—such as e-learning, Islamic applications, and interactive multimedia—has been shown to enhance student motivation, collaboration, and critical thinking, though it also presents ethical challenges such as digital distractions and reduced spiritual interaction. Standardization ensures the quality, direction, and consistency of Islamic education while remaining adaptive to societal changes. Overall, the study concludes that ideal Islamic education is holistic, balancing cognitive, affective, and psychomotor aspects, and capable of producing globally competitive Muslim generations without losing their Islamic identity. Thus, the development of methods, strategies, approaches, and standardization rooted in Qur’anic values and supported by digital technology is essential to achieving the true goals of Islamic education.